2018
DOI: 10.3892/ijmm.2018.3756
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of hepatic lipase is associated with decreased CD133 expression and clone formation in HepG2 cells

Abstract: The drug resistance of cancer remains a major obstacle to successful chemotherapy. New strategies for improving chemotherapeutic efficacy are urgently required. Recent studies have indicated that LIPC plays a role in promoting the liver metastasis of colorectal cancer. In the present study, we aimed to investigate the effects of LIPC on theproliferation and clone formation of colorectal cancer-derived cells, and chemoresistance in hepatoblastoma-derived HepG2 cells. The activity and expression of LIPC were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…The liver, as a digestive organ, is rich in a large amount of lipase 48–51 . HepG2 cells also exhibit a relatively higher lipase activity and expression levels compared to the other colon cancer cell lines 52 . According to gel electrophoresis experiments, better DNA release ability of the Bio‐PEG‐CN/DNA complex was found under the coexistence of lipase and weak acidity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The liver, as a digestive organ, is rich in a large amount of lipase 48–51 . HepG2 cells also exhibit a relatively higher lipase activity and expression levels compared to the other colon cancer cell lines 52 . According to gel electrophoresis experiments, better DNA release ability of the Bio‐PEG‐CN/DNA complex was found under the coexistence of lipase and weak acidity.…”
Section: Resultsmentioning
confidence: 99%
“…[48][49][50][51] HepG2 cells also exhibit a relatively higher lipase activity and expression levels compared to the other colon cancer cell lines. 52 According to gel electrophoresis experiments, better DNA release ability of the Bio-PEG-CN/DNA complex was found under the coexistence of lipase and weak acidity. In the presence of acidic tumor microenvironment and abundant lipase in hepatoma cells (HepG2), the lipid bonds of Bio-PEG-CN material could be hydrolyzed more rapidly to realize the release of nucleic acid drugs at the lesion site.…”
Section: Dna Condensation and Releasementioning
confidence: 97%
“…A recent study has shown that high expression of LIPG, another triglyceride lipase, is involved in TNBC metastasis through regulation of asymmetric cell division and maintenance of CSCs 16 . Moreover, down‐regulation of LIPC in HepG2 cells is associated with decreased expression of CD133, reduced cell proliferation and colony formation, as well as increased chemotherapy resistance 17 . CSCs are mainly responsible for the metastatic property of malignant cancers, 18 raising our interest in whether LIPH is involved in the behavioural regulation of CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…16 Moreover, down-regulation of LIPC in HepG2 cells is associated with decreased expression of CD133, reduced cell proliferation and colony formation, as well as increased chemotherapy resistance. 17 CSCs are mainly responsible for the metastatic property of malignant cancers, 18 raising our interest in whether LIPH is involved in the behavioural regulation of CSCs. We investigated whether LIPH plays an important role in the maintenance of CSCs and promotes metastasis in breast cancer cells.…”
Section: Liph Has Different Biological Functions Including Integrimentioning
confidence: 99%